Halo-derivatised calix[4]tubes. - Matthews, SE; Felix, V; Drew, MG; Beer, P (2003)
Halo functionalisation of calix[4]tubes has been investigated through both derivatisation of individual calix[4]arenes and calix[4]tubes, using classical synthetic methods, to allow preparation of a series of novel derivatives. The solution and solid state properties are in accordance with the constituent[4]arenes adopting flattened cone arrangements which on complexation with potassium simplify to a regular cone. Electrospray and 1H NMR studies, combined with molecular modelling have been used to ascertain the metal binding of this new series of cryptand like ionophores, demonstrating their retained selectivity for binding potassium over other Group 1 metals and the dependence on counter anion in the weak binding of silver.